2020
DOI: 10.1111/ics.12656
|View full text |Cite
|
Sign up to set email alerts
|

Emollient structure and chemical functionality effects on the biomechanical function of human stratum corneum

Abstract: OBJECTIVE: Cosmetic emollients are widely used in skincare formulations due to their ability to 'soften' the skin and modulate formulation spreadability. Though emollients are commonly used, little is known about their effects on the biomechanical barrier properties of human stratum corneum (SC), which play a critical role in consumer perception of formulation efficacy. Accordingly, our objective was to provide new insights with a study involving fourteen cosmetic emollient molecules with widely varying struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 44 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…Previous studies have shown a strong connection between volume taken up by either water molecules or formulation components inside the SC and resulting drying stress. 22 Reduction in volume (i.e., losing water, lipids or proteins) is closely associated with an increase in stress while gaining volume (i.e., from water or components entering the SC) is related to a decrease in stress. Cleansers are known to strip lipids, particularly fatty acids, from the SC 13,23 and are expected to increase stress and perception of tightness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown a strong connection between volume taken up by either water molecules or formulation components inside the SC and resulting drying stress. 22 Reduction in volume (i.e., losing water, lipids or proteins) is closely associated with an increase in stress while gaining volume (i.e., from water or components entering the SC) is related to a decrease in stress. Cleansers are known to strip lipids, particularly fatty acids, from the SC 13,23 and are expected to increase stress and perception of tightness.…”
Section: Discussionmentioning
confidence: 99%
“…We find that stiffness, film stress, and reported tightness all noticeably decrease following application of the moisturizer. This corresponds with an increase in penetration volume as not only do moisturizing components diffuse into the SC, but these hygroscopic molecules are also able to capture and retain water 22 . Furthermore, Osmoskin® contains 68% water and a mix of glycols, effectively dosing the skin with extra hydration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emollients are added to formulations for the purpose of improving spreadability, improving skin feel, as well as improving the hydration function of the SC [59][60][61]. The softening of skin brought about by emollients is attributed to the formation of an occlusive film on the skin that renders a reduced TEWL [62].…”
Section: Emollients and Humectantsmentioning
confidence: 99%
“…Emollients do not only enhance the character of the applied vehicle but also promote dermal penetration of incorporated drug(s) [63]. Moreover, emollients have demonstrated the capacity to reduce stress experienced by the SC, such as injuries or wounds, by penetrating the SC and replacing the lost water volume [61]. This emphasizes the profound relationship between the transport properties provided by emollients and their beneficial effect on repairing the barrier function of the outermost skin layer [61].…”
Section: Emollients and Humectantsmentioning
confidence: 99%